2022
DOI: 10.1155/2022/3380609
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm of Apriori-Based Rural Tourism Driving Factors and Its System Optimization

Abstract: Rural tourism, as a vital component of tourism, is critical to the development of rural economies, farmers’ income, rural civilization, new rural construction, and urban-rural interaction. Simultaneously, as the size and complexity of data sets grow larger, how to improve the efficiency of association rule algorithms for mining large data sets has become a hot topic in association rule mining. Rural tourism development that is cultural and creative not only contributes to rural revitalization, but also to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In a study focusing on inbound tourists to China, the algorithm was used to identify co-occurring preference attributes at scenic spots, and based on these attributes, market segmentation was conducted, offering profound insights into the tourism market [ 61 ]. And the Apriori algorithm demonstrates significant potential in uncovering relationships between tourism destinations and holds value in understanding and promoting the development of rural tourism, among other areas [ 62 ]. This method not only assists researchers in identifying key driving factors but also provides scientific decision-making support for the formulation and implementation of tourism policies.…”
Section: Methodsmentioning
confidence: 99%
“…In a study focusing on inbound tourists to China, the algorithm was used to identify co-occurring preference attributes at scenic spots, and based on these attributes, market segmentation was conducted, offering profound insights into the tourism market [ 61 ]. And the Apriori algorithm demonstrates significant potential in uncovering relationships between tourism destinations and holds value in understanding and promoting the development of rural tourism, among other areas [ 62 ]. This method not only assists researchers in identifying key driving factors but also provides scientific decision-making support for the formulation and implementation of tourism policies.…”
Section: Methodsmentioning
confidence: 99%
“…Li [54] argued that the drivers of rural tourism development have five sub-systems: supply, demand, decision, media, and support. Xiao [55] suggested that the core drivers of rural tourism development are demand, supply, marketing, and support forces. Wang et al [56] divided the tourism drivers for rural revitalization into endogenous and exogenous drivers.…”
Section: Research Lineage Of Tourism Development Driversmentioning
confidence: 99%